In Vitro Anti-inflammatory Activity of Bamboo Tali Leaf (Gigantochloa apus) Ethanol Extract - Hidayah, Nurul; Hafshah, Mutista (Biology, Medicine, & Natural Product Chemistry, 2023)
Inflammation is a physiological process that serves as a defense mechanism for the body against foreign substances, bacteria, or irritants. Inflammation can be cured with anti-inflammatory drugs. One of the plants that has the potential to be an anti-inflammatory agent is the bamboo leaf. This research aims to analyze the content of secondary metabolites, determine the inhibition value and IC50 value of the anti-inflammatory activity of the ethanol extract of bamboo tali leaves. Bamboo tali leaves were macerated using 96% ethanol and subjected to phytochemical screening. The extract was then tested for anti-inflammatory activity in vitro with the Bovine Serum Albumin (BSA) protein denaturation inhibition method. Bamboo tali leaf ethanol extract contains flavonoids, alkaloids, saponins, and phenols. The anti-inflammatory activity of the ethanol extract of bamboo tali leaves with concentrations of 28, 42, 56, 70, and 84 ppm had an inhibition percentage value of 23.14 ± 0.008%; 34.30 0.026%; 54.51 0.060%; 69.07 ± 0.006%; and 87.02 ± 0.021% with an IC50 value of 52.991 ppm. These results indicate that the ethanol extract of bamboo tali leaves has the potential to be an anti-inflammatory with a strong IC50 value below 100 ppm.